Tsunami sedimentary deposits of Crete records climate during the 'Minoan Warming Period' (≈3350 yr BP). (June 2018) - Lécuyer, Christophe; Atrops, François; Amiot, Romain; Angst, Delphine; Daux, Valérie; Flandrois, Jean-Pierre; Fourel, François; Rey, Kevin; Royer, Aurélien; Seris, Magali; Touzeau, Alexandra; Rousseau, Denis–Didier
Earthquakes or explosive eruptions generate tsunami, which are at the origin of thick and chaotic coastal sediments. These commonly fossiliferous deposits are formed instantaneously at the historical or geological timescale and therefore have the potential to provide snapshot records of past climates. In Crete, near the city of Palaikastro, crops out a 1- to 9-m-thick sedimentary layer deposited by a huge tsunami that has been previously estimated to be about 9 m high. The presence of volcanic ash, the geometry, the archeological and faunal contents of the sedimentary deposit along with radiocarbon dating converge for interpreting this tsunamite as coeval with the Minoan Santorini (Thera) eruption ≈3350 yr BP. During its drawback, the tsunami deposited rocky blocks and a muddy matrix containing mollusc shells dredged from the seabed as well as cattle skeletal remains and various artifacts belonging to the contemporaneous Minoan civilization. While the oxygen isotope compositions of terrestrial vertebrate bone remains most likely resulted from diagenetic alteration, those of a bovid tooth revealed that air temperatures during MM3 and LM1 periods were about 4°C higher than nowadays. Oxygen isotope measurements of marine mollusc shells also revealed that sea surface temperatures were higher by about 2°C. Those results compare with the 2.5°C temperature difference already estimated according to both δ 2 H and δ 18 O values of Greenland ice cores. Incremental sampling of marine gastropods and bovid teeth suggests that the seasonal amplitude was similar to that prevailing during the second half of the 20th century.